Advanced Nursing Practice in Rural Areas: Connectedness versus Disconnectedness - Margaret M. Conger; Karen A. Plager (Rural Nurse Organization; Binghamton University, 2012)
Scarcity of health care providers leads to reduced access to health care for rural residents. Better understanding of constraints confronting nurses in rural practice is needed. Our program prepares Advanced Practice Nurses (APNs) to work in rural areas. Using interpretive phenomenology we studied program terminal outcomes as practiced by our APN graduates. Individual interviews and focus groups were conducted with graduates who had been in practice for at least one year. This paper describes one theme - rural connectedness versus disconnectedness- that was uncovered in the larger study. Elements leading to rural connectedness included development of support networks, relationships with urban health care centers, connections with local communities, and support through electronic means. Rural disconnectedness resulted from lack of relationships with other health care providers, lack of mentors and support staff, and the absence of electronic support. Implications for education for rural advanced practice are discussed.